2021
DOI: 10.1111/cbdd.13934
|View full text |Cite
|
Sign up to set email alerts
|

Novel candidates in the clinical development pipeline for TB drug development and their synthetic approaches

Abstract: Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis (Mtb) and one of the deadliest infectious diseases in the world. Mtb has the ability to become dormant within the host and to develop resistance. Hence, new antitubercular agents are required to overcome problems in the treatment of multi-drug-resistant Tb (MDR-Tb) and extensively drug-resistant Tb (XDR-Tb) along with shortening the treatment time. Several efforts are being made to develop very effective new drugs for Tb, within the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 163 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…Kumar et al (2021)77 suggested controlling TB by 2030. Health professionals must ensure the following strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al (2021)77 suggested controlling TB by 2030. Health professionals must ensure the following strategies.…”
mentioning
confidence: 99%
“…Subsequently, the spread of infection drastically reduced. Furthermore, government agencies and non-government voluntary working groups in the field must exterminate paucity, improve access to healthcare, ensure adequate protection, and strengthen communities to develop robust policies and systems to stop TB77 . Figure1depicts history and principal findings of this paper.…”
mentioning
confidence: 99%
“…Moreover, multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) are spreading worldwide, causing major global health issues . Therefore, much effort has been made to develop effective new drugs for the treatment of TB . As a result, the first MDR antituberculosis drug bedaquiline (BDQ), a new ATP synthase inhibitor, was approved by the FDA in 2012 as the first antituberculosis-specific drug .…”
mentioning
confidence: 99%
“… 2 Therefore, much effort has been made to develop effective new drugs for the treatment of TB. 3 As a result, the first MDR antituberculosis drug bedaquiline (BDQ), a new ATP synthase inhibitor, was approved by the FDA in 2012 as the first antituberculosis-specific drug. 4 This also paved the way for medicinal chemists to discover new ATP synthase inhibitors that were more effective and potent against MDR/XDR-TB.…”
mentioning
confidence: 99%